PENGGUNAAN MEDIA BONEKA DI KELAS AWAL PADA MADRASAH IBTIDAIYAH - Yayan Carlian; Rika Siti Yulianti (Jurusan Pendidikan Guru Madrasah Ibtidaiyah, 2018)
The research objective of this class action is to determine student learning outcomes before using the media three-dimensional, the use of three-dimensional media, and student learning outcomes by using three-dimensional media on the subject matter of the attitude of harmony and help each other in class III MI Al-Islah. The method used in this research is a classroom action research. The study consisted of III cycles where each cycle consists of planning, action, observation, and reflection. Based on the results obtained can be summarized as follows: 1) student learning outcomes before using a three-dimensional media is still low, with an average value of 70.03 with 46% mastery learning; 2) the use of three-dimensional media in each cycle has risen in the first cycle of teacher activity 44%, cycles II 69%, 81% the third cycle, shile the activity of the first cycle students 42%, 67% the second cycle and the third cycle of 67%; 3) the results of student learning outcomes by using the doll media in each cycle has increased. In the first cycle with an average of 73.21 completeness study 54%, then the second cycle with an average of 76.60 completeness study 82%, and the third cycle reach the average grade is 81.43 with 89% mastery learning.